Karya Ilmiah Tugas Akhir Mahasiswa (Kitam) Pengaruh Lingkungan Kerja dan Jam Kerja Terhadap Produktivitas Kerja - Evan Alif Pranajaya Putro Nugroho; Muhamad Alwi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of work environment and working hours on employee productivity at CV Sumber Cor. The research employs a quantitative approach with an associative research design. The population consists of 63 employees, all of whom were selected as the sample using a saturated sampling technique. Data were collected through questionnaires and analyzed using validity and reliability tests, as well as multiple linear regression analysis with SPSS. The results indicate that the work environment has a positive and significant effect on employee productivity. Working hours also have a significant effect on productivity, where well-structured and non-excessive working hours improve efficiency, while excessive working hours may reduce productivity due to fatigue. Simultaneously, work environment and working hours significantly affect productivity, contributing 51.3% to the variation in employee productivity. This study highlights that improving employee productivity can be achieved by creating a conducive work environment and implementing effective and balanced working hour management.